Kate Bernheimer’s the Gold Sisters Trilogy in the Context of a Feminist Deconstruction of Fairy-tale Discourse - Alexandra I. Kameneva (Литература двух Америк, 2025)
The article examines the emergence of feminist understanding of fairy-tale discourse in the second half of the 20th century and its development to the present. In the analysis of critical works by European (S. de Beauvoir, M.-L. von Franz) and American (M. Lieberman, K. Rowe, M. Kolbenschlag, K. Stone, J. Zipes, H. Pilinovsky) researchers reflecting on the issues of representation of women in fairy tale texts and their animated adaptations, the psychological and social aspects, the centuries-old imposition of passivity on women as the main virtue and a happy marriage as the only available benefit were identified as the most acute aspects of fairy tales. The contemporary American writer Kate Bernheimer becomes the successor of the ideas of feminist researchers. The author’s creative method, which consists of transforming the plots of German, Russian and Yiddish fairy and folk tales, implemented in the trilogy about the Gold sisters, is intended to highlight the most problematic ideas and then deconstruct them: in the novel The Complete Tales of Ketzia Gold a consistent criticism of the established principle “and they lived happily ever after” is made; in the novel The Complete Tales of Merry Gold, due to the author’s active appeal to the tales from Afanasiev’s collection, the idea that beauty and hard work are the guarantors of the well-being of the fairy-tale heroine is debunked; in the novel The Complete Tales of Lucy Gold the traditional fairy-tale plot scheme of the happy fate of the third child is destroyed. The Gold sisters’ novels do not have a happy ending, a “eucatastrophe”, and the trilogy, which Bernheimer conceived as a collection of fairy tales, destroys the “happy ending” trope characteristic of popular fairy tales, thereby demonstrating, on the one hand, the dystopian nature of the modern fairy tale, and, on the other, its opposition to American popular culture.